Clinical Value of Screening Peritoneal Dialysis Patients for Bacterial Colonization or Contamination. Issue 2 (March 2019) - Parthasarathy, Rajeevalochana; Kashem, Tasnuva; NicFhogartaigh, Caoimhe; Melzer, Mark; Fan, Stanley L.
Introduction: The adoption of the International Society for Peritoneal Dialysis guideline of using mupirocin ointment has been limited by fear of developing mupirocin-resistant organisms. We performed a surveillance program of a large peritoneal dialysis (PD) unit. Methods: We performed 1, 175 surveillance swabs from anterior nares, PD catheter exit site, groin, and axilla, from 240 patients. The mean interval between swabs was 3.3 months. Results: Colonization by Staphylococcus aureus ( S. aureus ) or Pseudomonas species was 9.5% and 10.9%, respectively. Despite adopting a universal policy of applying mupirocin to PD catheter exit sites in 2001, no instances of mupirocin-resistant S. aureus were identified. Moreover, patients who grew S. aureus from surveillance swabs did not experience higher peritonitis rates than those with "no growth." This was in contrast to patients who grew Pseudomonas or enteric organisms. There were no differences in patient demographics for those who grew S. aureus, Pseudomonas, or enteric organisms (compared with "no-growth" patients). Conclusion: Our results suggest that the application of mupirocin ointment appeared to minimize peritonitis of patients colonized with S. aureus. The use of mupirocin in this patient cohort has not led to mupirocin resistance. The increased peritonitis rate of patients who grew Pseudomonas or enteric organisms is of interest. We propose that greater attention to hygiene and catheter care in these patients is warranted. The increasing use of paid healthcare workers attending patients daily to help perform PD (assisted PD) gives an opportunity for us to address these wider issues.